Gentoo penguins as sentinels of climate change at the sub-Antarctic Prince Edward Archipelago, Southern Ocean. (June 2019) - Carpenter-Kling, T.; Handley, J.M.; Connan, M.; Crawford, R.J.M.; Makhado, A.B.; Dyer, B.M.; Froneman, W; Lamont, T.; Wolfaardt, A.C.; Landman, M.; Sigqala, M.; Pistorius, P.A.
Highlights: Climate change models have predicted a southward migration of the SAF. The diet of resident gentoo penguins at the Prince Edward Archipelago (PE) is highly variable. Prey assemblage within the diet varies with the position of the sub-Antarctic front (SAF). These penguins are important sentinel species for the local marine ecosystem at PE. Regular sample collection will allow for variability in the ecosystem to be monitored. Abstract: Some upper trophic level predators, such as marine mammals, seabirds and large predatory fish have been shown to be useful sentinels for marine ecosystems. Through their demography, diet and foraging behaviour, ecosystem changes associated with climate change can be monitored. The local marine ecosystem at the Prince Edward Archipelago in the Southern Indian Ocean is heavily influenced by the position of the dynamic sub-Antarctic front (SAF) that varies inter-annually in terms of its influence on the local environment. If the SAF migrates southwards, as climate change models have predicted, the abundance of autochthonous and allochthonous prey found within the vicinity of the archipelago will decrease and increase, respectively. We investigated the diet of an inshore forager at the archipelago, the gentoo penguin Pygoscelis papua, as a possible sentinel to the expected changes in the prey assemblages in local waters, due to the southward migration of the SAF. We collected stomach content samples from gentoo penguins, using the water off-loading technique, monthly over three years (1994–1996) and then annually during 2012, 2014 and 2015. Prey assemblages within the diet was found to coincide with the proximity of the SAF to the Prince Edward Archipelago as well as the annual life cycles of prey. Due to the plasticity these penguins exhibit in their diet and foraging behaviour, we suggest that they are important sentinel species for the local marine ecosystem of the Prince Edward Archipelago. Regular sample collection from these birds, albeit stomach content samples and/or tissues for stable isotope analysis, should be collected so that variability in the ecosystem can be easily monitored.